Trabalho em equipe e integralidade num cenário hospitalar - Sanches, Sarita Barbosa [UNIFESP] (2015)
The present research aims to understand and analyze how a team of a hospital unit works on the prospect of a full attendance. The option was for an exploratory and qualitative case study, whose production data was collected by means of observations recorded in field journal and meetings with professionals with semi structured interviews and conversation, as well as informal conversations with patients and documentary analysis. In the meetings, were discussed issues related to the organization of work, the mode of operation of the team, the problems involved for the production of integral care and continuity of care. Our study showed that the team working in this hospital scenario presents many difficulties and is still a challenge. The organization of the work process, vertical and fragmented, does not contribute to joint performances of professionals. The professional area has an organization of its own and, in general, performs their work in a isolated manner from other areas. There are very few spaces for exchange of information, to discussions of cases and planning joint interventions. The care of patients is more focused on performing procedures than listen and dialogue with their living conditions. The issues that emerged from the investigation indicate the need for changes in the organization of the work process in the hospital, with the deployment of strategies that contribute to better coordination between the different professionals who work there, among them we highlight the deployment of team meetings and moments of permanent education. Also indicate the importance of the participation of management in these transformations for producing integral care.